Mechanical Properties of a PLA/Nettle Agro-Composite with 10% Oriented Fibers - Bogard, Fabien; Bach, Thierry; Bogard, Virginie; Beaumont, Fabien; Murer, Sébastien; Bliard, Christophe; Polidori, Guillaume (Applied Sciences, 2022)
Within the framework of the environmental policies which tend toward new ecological materials, without the use of petroleum-based materials, the objective of this work is to develop a composite 100% natural associating fibers of European nettles (Urtica Dioica) and PLA (Poly-Lactic Acid). After having determined the properties of both components of the new composite, a methodology was implemented to maximize the PLA/nettle association. Then, tensile tests with standardized specimens were carried out to assess the mechanical characteristics of this new composite, which are ultimately very dependent on its manufacturing process. Experimental results demonstrated that the manufacturing process results in a material with enhanced overall mechanical properties, compared to those found in the literature (Young’s modulus: 5.41 ± 0.23 GPa vs. 1.2 to 4.37 ± 0.14 GPa). Our findings suggest widespread use of this PLA/nettle composite, although its properties clearly stem from the quality of the nettle fiber, which is itself highly dependent on variable parameters linked to the growing conditions of the plant. The possible applications of this eco-friendly material seem to be very wide, as long as they do not have to undergo too important structural loads, as for example the sector of interior furniture, packaging, or even interior elements in the automotive sector.
Number: 19
Keywords: PLA; fiber nettle; mechanical properties; process